2016
DOI: 10.1021/acs.jced.5b01082
|View full text |Cite
|
Sign up to set email alerts
|

New Mechanism and Model of Butyric Acid Extraction by Phosphonium Ionic Liquid

Abstract: A new model of the liquid/liquid equilibrium of butyric acid (BA) and water extraction from aqueous solutions to an organic solvent containing phosphonium ionic liquid and dodecane has been derived. It has seven fitting parameters and describes experimental data well. Reactive extraction with formation of the (p, 1) acid-IL complexes with p ≤ 11 acids on one hand and their aggregation by water bridges on the other hand refer to the dualistic character of the extraction process and the developed model. The valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
83
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(96 citation statements)
references
References 51 publications
13
83
0
Order By: Relevance
“…Kashin et al showed that even with an IL miscible in all ranges with water, at the microscopic level, the system organizes itself in hydrophilic and hydrophobic domains. 39 In line with these observations, aggregate formation with carboxylic acids, thus micro-structuring is expected for [P 666,14 ][Phos] as well, as suggested by Marták et al 40,41 To understand the effects of micro-structuring and intermolecular interactions in the [P 666,14 ][Phos] phase on the behavior and recoverability of HAc, IL-HAc mixtures of varying Z were studied with FT-IR, 31 P NMR, and 1 H NMR. The degree of proton transfer and hydrogen bonding between HAc and the [Phos] − anion were monitored.…”
Section: Characterization Of Hac-loaded Il Phasessupporting
confidence: 65%
See 2 more Smart Citations
“…Kashin et al showed that even with an IL miscible in all ranges with water, at the microscopic level, the system organizes itself in hydrophilic and hydrophobic domains. 39 In line with these observations, aggregate formation with carboxylic acids, thus micro-structuring is expected for [P 666,14 ][Phos] as well, as suggested by Marták et al 40,41 To understand the effects of micro-structuring and intermolecular interactions in the [P 666,14 ][Phos] phase on the behavior and recoverability of HAc, IL-HAc mixtures of varying Z were studied with FT-IR, 31 P NMR, and 1 H NMR. The degree of proton transfer and hydrogen bonding between HAc and the [Phos] − anion were monitored.…”
Section: Characterization Of Hac-loaded Il Phasessupporting
confidence: 65%
“…3. A similar interaction was previously proposed, 40 but it did not consider protonation of the anion [Phos] − . To study the effect of dilution with an apolar co-solvent on the HAc-IL interactions, the FT-IR and 31 P NMR spectra were also measured for several IL-HAc-DoD solutions with varying Z.…”
Section: Characterization Of Hac-loaded Il Phasesmentioning
confidence: 70%
See 1 more Smart Citation
“…The tetraalkylphosphonium orthoborate ILs exhibit outstanding friction reducing and anti‐wear performance in tribological contacts with a wide variety of solid materials, and thus are attractive as alternative high‐performance lubricants and lubricant additives in tribology . The functional performance of ILs in tribological applications is rationalized by distinct ion structures of tetraalkylphosphonium cations and their preferential associations with anions and molecular solvents in IL matrices . It has been well demonstrated from experimental and computational perspectives that mesoscopic liquid organizations of trihexyltetradecylphosphonium ([P 6,6,6,14 ]) ILs are dominated by three distinct landscapes at different length scales associated with short range adjacency correlations, positive‐negative charge alternations at intermediate range, and long‐ranged polarity ordering correlations .…”
Section: Introductionmentioning
confidence: 99%
“…with the tuneable properties of ILs to provide these new materials with unprecedented characteristics. Several types of IL‐based separation membranes have been studied, including supported IL membranes (SILMs), pIL membranes, polymer/IL gel membranes and membrane contactors that employ ILs as absorbents . In general, ILs achieve separation through physisorption of gas or vapours and, if functional groups are present in the IL structure, then both physical and chemical sorption combine to enhance the separation performance.…”
Section: Ionic‐liquid Catalytic Membranesmentioning
confidence: 99%